Avaliação de microbacias hidrográficas para a conservação de áreas ripárias - Santos, Rafael Marini Paschoaletti Perri dos (2017)
Nowadays, society has a challenge to deal with sustainable water use. High demand and water contamination, environmental degradation and the unpredictability of climate changes are some water insecurity causes. Riparian forests maintenance offers water ecosystems services, but in some cases the riparian ecosystem is in a degraded condition that require human intervention actions for forest restoration. In this way, geotechnologies help us to infer about physical landscape characteristics where watershed is a basic unity for environmental planning. This study aimed to identify important hydrologically areas of Consulta stream watershed and Retiro stream watershed and propose priorities areas for forest restoration and sustainable agricultural destination. The two watersheds are the main sources of public water supply in the city of Bebedouro (Brazil). It is hypothesized that the limits established by Brazilian forest law (BFL) riparian buffers zones may not fully guarantee the two watersheds riparian areas protection. It was assumed that the forest community plays an important role in the attenuation of chemical elements and sediments, and that is essential that there is a disruption of potentially polluting activities near riparian areas. It was used in the study images from orbital sensors spatial resolution 30 m and 90 m and topographical map 1:50.000 for obtaining and processing elevations data and land use in geographic information system (GIS), and environmental legislation. The results allowed to characterize the watersheds that are surrounding and presented similarities in their physical parameters (basin form, drainage density, channel length, and others) and the Topographic Wetness Index (TWI) class distribution, slope class, landscape elements and land use. Three scenarios of priority areas for forest restoration were generated. It was observed that the priority areas are distributed close to the drainage channel of watersheds and are partially related to required areas by BFL. It can be concluded that in the three scenarios established the BFL may not be sufficient for the full protection of riparian sites and the adopted methodology proved to be efficient for guiding water resources management actions at larges scales.